2009
DOI: 10.1103/physrevlett.103.257201
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Modeling of MultiferroicRMn2O5

Abstract: We investigate the phase diagrams of RMn(2)O(5) via a first-principles effective-Hamiltonian method. We are able to reproduce the most important features of the complicated magnetic and ferroelectric phase transitions. The calculated polarization as a function of temperature agrees very well with experiments. The dielectric-constant step at the commensurate-to-incommensurate magnetic phase transition is well reproduced. The microscopic mechanisms for the phase transitions are discussed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 27 publications
2
73
0
Order By: Relevance
“…We calculate the ordering temperature by forcing all exchange interactions to be ferromagnetic, and get T c = 311 K by a Monte Carlo simulation. This temperature is only about 1.5 times greater than the T c of the AFM1 phase from simulations (In RMn 2 O 5 [27], the ratio is approximately 3 -4. ), which also indicate that the spin frustration is weak in CuO.…”
Section: −5åmentioning
confidence: 69%
“…We calculate the ordering temperature by forcing all exchange interactions to be ferromagnetic, and get T c = 311 K by a Monte Carlo simulation. This temperature is only about 1.5 times greater than the T c of the AFM1 phase from simulations (In RMn 2 O 5 [27], the ratio is approximately 3 -4. ), which also indicate that the spin frustration is weak in CuO.…”
Section: −5åmentioning
confidence: 69%
“…This indicates that the inverse DzyaloshinskiiMoriya (DM) interaction, ∼e i j ×(S i ×S j ), contributes only 1 nC/cm 2 (<1%) to the net polarization. Thus, the exchangestriction mechanism of a (S i ·S j ) type is the origin of the magnetically induced polarization in o-TMO [11][12][13][14].…”
Section: Resultsmentioning
confidence: 98%
“…reported the magnetostructural phase diagram of o-TMO as a function of temperature and * jhlee.david@gmail.com † hmjang@postech.ac.kr magnetic field by using neutron diffraction measurements. The ground-state structural, electronic, and magnetic properties of o-TMO were subsequently investigated by employing first-principles density-functional theory (DFT) calculations [11][12][13][14]. These ab initio studies confirmed that the groundstate structural symmetry of o-TMO is P b2 1 m and the ferroelectricity in o-TMO is driven by the nearly collinear spin ordering that breaks the centrosymmetry without invoking the spin-orbit coupling.…”
Section: Introductionmentioning
confidence: 90%
“…[18]. The major difference between the current model and previous ones [17,18] is that we include here the single ion easy axis anisotropy K 3 for Mn 3+ ions and the easy plane anisotropies D i for Mn…”
mentioning
confidence: 93%